The effect of Dimethyl Sulfoxide (DMSO) on the development of 10-days chicken embryo based on body length and head diameter - Pratiwi, Herlina; Wardana, Analis Wisnu; Okatvianie A.P, Dyah Ayu; Haryo, Albiruni; Fauziah, Nayo Diah; Abqariyyan, Rizky Pamwidya; Aditia, Rifkytri; Afra, Syadza (Faculty of Animal Science, Universitas Brawijaya, 2020)
This research aims to understand the effect of dimethyl sulfoxide (DMSO) on the body length and head diameter of chicken embryos. The samples used in this research were 3 days chicken egg embryos weighed at 55 g. The samples were divided into two groups, the control group (without DMSO) and treatment group (injected with 0.25 mL of 2% DMSO). Each group was incubated at 38oC for 10 days, and the observed variables were embryos body length and head diameter through macroscopic observation. The results showed that 2% DMSO did not affect the embryos body length, but increase its head diameter. The research concludes that DMSO can be used as chemical solvent with consideration of its effect on the increased embryos head diameter.